The role of renewable energy in addressing climate change concerns: an assessment study - Akbaba, Mehmet Fatih (TAYLOR & FRANCIS INC, 2024)
The current study examines the relationships among well-being, attitudes toward wind energy, and climate change hope in adolescents, using the participant recruitment method. The study involves a sample of 435 high school students, aged 13 to 18. A digital questionnaire is disseminated to collect the required data. Descriptive statistics, correlation analysis, independent t-tests, and structural equation modeling are used to explore these relationships. The results indicate that adolescent well-being is positively correlated with both wind energy attitudes (r = .254, p < .001) and climate change hope (r = .321, p < .001). Structural equation modeling indicates that climate change hope mediates the relationship between renewable energies and well-being. Furthermore, the analysis shows no significant gender differences in well-being or attitudes toward wind energy however, it highlighted a significant gender disparity in climate change hope, with females reporting higher levels than males. The study results in no marked differences in attitudes toward wind energy or climate change hope based on perceived socio-economic status. However, a gradient effect is observed in well-being across different socio-economic statuses, which underscores the importance of integrating environmental education and promoting renewable energy initiatives to nurture a hopeful perspective toward climate change among adolescents.
Keywords: Renewable energy; energy source; climate change; education; students; wind energy; FEASIBILITY; TECHNOLOGY; SYSTEMS; HEALTH; IMPACT; POLICY; Energy & Fuels; Engineering; Environmental Sciences & Ecology